Asymptotic scalability analysis of mobility protocols based on signalling overhead. (29th June 2011) - Hossain, Md. Shohrab; Atiquzzaman, Mohammed
Increasing demand for mobility in wireless data networks has given rise to various mobility management protocols. The protocols use signalling messages to maintain reachability of mobile nodes. Increase in the number of mobile nodes gives rise to the scalability issues that need to be dealt with to avoid performance degradation of the network. In this paper, we have developed analytical models to obtain the asymptotic mobility signalling overhead on mobility management entities of two mobility protocols in terms of network size, mobility rate and traffic rate. These asymptotic overhead models have been used to compute mobility scalability factors of the protocols. We have presented numerical parameters to validate the analytical model. Results show that the mobility protocols exhibit asymptotically identical mobility signalling overhead on the network.